Influence of social media on cosmetic facial surgeries among individuals in Kuwait: employing the theory of planned behavior - Alduosari, Madhawi; Albuloshi, Thurayya; Alsaber, Ahmad; Al Saeed, Farah; Alkandari, Anwaar; Anbar, Amal; Alboloushi, Bedour; Helmy, Yasser (Frontiers in Digital Health, 2025)
IntroductionThe increasing popularity of cosmetic facial surgeries among Kuwaiti youth has been significantly influenced by social media. Platforms such as Instagram and TikTok propagate beauty ideals that may lead to heightened interest in aesthetic procedures. This study investigates the impact of electronic word-of-mouth (e-WOM), content marketing (CM), and influencer marketing (IM) on attitudes (ATT), subjective norms (SN), perceived behavioral control (PBC), and intention (INT) to undergo cosmetic surgery, using the Theory of Planned Behavior (TPB) framework.MethodsA cross-sectional quantitative design was employed involving 730 participants (84.9% female), selected using convenience sampling across universities, clinics, and workplaces in Kuwait. A validated TPB-based questionnaire measured constructs such as ATT, SN, PBC, INT, health consciousness, and social media influences (e-WOM, CM, IM). Data were analyzed using Structural Equation Modeling (SEM) via SmartPLS. Reliability and validity were confirmed using Cronbach's alpha, composite reliability, average variance extracted (AVE), and discriminant validity.ResultsSubjective norms significantly influenced perceived behavioral control (β = 0.336, p < 0.001), which in turn predicted intention to undergo cosmetic surgery (β = 0.316, p < 0.001). Attitude also positively influenced PBC (β = 0.298, p < 0.001). e-WOM had the strongest impact on ATT (β = 0.427, p < 0.001) and SN (β = 0.292, p < 0.001), followed by significant but smaller effects from CM and IM. The model demonstrated good fit, explaining 47.3% of the variance in INT.DiscussionSocial media plays a central role in shaping cosmetic surgery intentions among Kuwaiti youth, with subjective norms being the strongest predictor. These findings underscore the importance of societal expectations, particularly in collectivist cultures. Regulatory frameworks and educational campaigns are recommended to address ethical marketing practices, enhance digital health literacy, and promote realistic beauty standards.